2022
DOI: 10.1002/mnfr.202100751
|View full text |Cite
|
Sign up to set email alerts
|

Lariciresinol Displays Anti‐Diabetic Activity through Inhibition of α‐Glucosidase and Activation and Enhancement of Insulin Signaling

Abstract: Scope: The aim of this study is to investigate the antidiabetic effect of lariciresinol (LSR) in C2C12 myotubes and streptozotocin (STZ)-induced diabetic mice. Methods and results: To investigate antidiabetic potential of LSR, 𝜶-glucosidase inhibitory assay, molecular docking, glucose uptake assay, western blot assay on antidiabetic biomarkers are performed. STZ-induced diabetic model is used for in vivo study by calculating oral glucose tolerance test, histochemical examination, and glycogen assay. LSR inhib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…As shown ( Figure 6 C), diabetic control animals (G2) exhibited extensive islet shrinkage and lower numbers of islet cells in the pancreas when compared with control animals (G1), whereas G4 animals (TRDI; 150 mg/kg) exhibited islet cells, normal acini cells, and few pancreatic cell regeneration foci. As excess glucose is stored as glycogen in the liver and skeletal muscle [ 30 ], we examined glycogen levels in skeletal muscle in the STZ-induced diabetic mice. As indicated ( Figure 6 D,E), glycogen levels in the skeletal muscle had increased significantly in G4 when compared with G2 and G3.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As shown ( Figure 6 C), diabetic control animals (G2) exhibited extensive islet shrinkage and lower numbers of islet cells in the pancreas when compared with control animals (G1), whereas G4 animals (TRDI; 150 mg/kg) exhibited islet cells, normal acini cells, and few pancreatic cell regeneration foci. As excess glucose is stored as glycogen in the liver and skeletal muscle [ 30 ], we examined glycogen levels in skeletal muscle in the STZ-induced diabetic mice. As indicated ( Figure 6 D,E), glycogen levels in the skeletal muscle had increased significantly in G4 when compared with G2 and G3.…”
Section: Resultsmentioning
confidence: 99%
“…DM is a multifaceted metabolic condition with several negative health implications. To combat this, extensive methods and therapeutics are used to improve glycemic control such as insulin sensitizers, insulin secretagogues, and prandial glucose regulators [ 30 ]. However, some drugs elicit serious side effects in patients with poor tolerance.…”
Section: Discussionmentioning
confidence: 99%
“…Proteins were separated according to their molecular weight using 10% SDS gel electrophoresis, followed by the transfer of bands to nitrocellulose membranes for 2 h. A 5% bovine serum albumin (BSA) was added to the membrane and incubated overnight at 4 °C with the first antibody, followed by incubation with a secondary antibody (anti-goat IgG). Bands were detected using a chemiluminescence system (PerkinElmer) [ 29 ].…”
Section: Methodsmentioning
confidence: 99%
“…α-Glucosidase breaks down oligosaccharides into monosaccharides, which are taken into the bloodstream from the colon. 4,5 Therefore, α-glucosidase inhibitors can effectively reduce postprandial hyperglycaemia after a mixedcarbohydrate diet and treat DM. Mounting evidence revealed that many plant species' therapeutic properties, such as antidiabetic, anticancer, antiaging, and antimelanin activities, are attributed to antioxidant polyphenolics.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, α‐glucosidase is a crucial enzyme for diabetes mellitus (DM). α‐Glucosidase breaks down oligosaccharides into monosaccharides, which are taken into the bloodstream from the colon 4,5 . Therefore, α‐glucosidase inhibitors can effectively reduce postprandial hyperglycaemia after a mixed‐carbohydrate diet and treat DM.…”
Section: Introductionmentioning
confidence: 99%